Classification of Tidal Inlets Along the Central East Coast of India. (2015) - Reddy, N. Amaranatha; Vikas, M.; Rao, Subba; Seelam, Jaya Kumar
Abstract: Coastal inlets are the openings along the coastline that provide a linkage between the open ocean and the hinterland water bodies. These coastal inlets are varied in nature depending on many influencing parameters such as tide, wind, river flow and waves. Amongst these parameters, the tides are the most regular while waves and freshwater flow are more seasonal. The tidal inlets have to be examined and studied to understand the nearshore coastal processes. The inlet remains stable (i.e. open) as long as the alongshore sediment bypasses the tidal inlet. Classification of coastal systems in a broader view is necessary for the management of tidal inlets. There are several methods to classify tidal inlets based on different perspectives namely geo-morphological, hydrodynamic etc. In the present study, tidal inlet classification is carried out considering the hydrodynamics and morphodynamics along the Andhra Pradesh coast, considering the classification method as in Hayes (1984) and Thuy (2013). The Hayes (1984) classification considers only the tidal range and significant wave height, whereas Thuy (2013) considers discharge due to tide (∼Tidal prism /tide duration) and wave (∼ ). A total of 108 tidal inlets along Andhra Pradesh coast on the east coast of India are classified considering annual mean wave height (Hs) as well as seasonal wave heights. This paper presents the methods used and results of the coastal classification along the central east coast of India.